A Correlation between Knowledge about Coral Reef Ecosystem and Marine Tourist Attitude toward Conservation at Pramuka Island, Kepulauan Seribu - Purbaya, Sharaswati; Komala, Ratna; Seribulan, M.N M (Biosfer: Jurnal Pendidikan Biologi, 2015)
Coral reef ecosystems are an ecosystem which important role both ecological and value. To conserve coral reef ecosystem requires knowledge form all the people especially marine tourist. Knowledge of coral reef ecosystems which is owned by marine tourist expected form conservation attitude of marine tourists to coral reef ecosystems. The aim of this research was to know the correlation knowledge of coral reef ecosystems with marine tourists conservation attitude around Pramuka Island, Kepulauan Seribu. This research was held on May 2015 at Pramuka Island. The research method used descriptive correlational. Population and sample were determined by simple random sampling of marine tourists on the Pramuka island with the criteria have experience of diving and diving activities in the Pramuka Island amounted to 80 divers. The instrument used was a questionnaire about their knowledge and attitudes of conservation by using a Likert scale. Hypothesis test using simple regression test and correlation test using the formula Pearson Product Moment. The result showed the equation Å¶ = 104,472+0,626X. The results showed there correlation between knowledge of coral reef ecosystems and conservation attitude marine tourists around Pramuka Island, Kepulauan Seribu with a correlation coefficient of 0,325.